SYNTHESIS, CHARACTERIZATION, AND APPLICATION OF ZnO/ZSM-5 AS CATALYST IN THE CRACKING PROCESS OF PALM METHYL ESTERS - Haryani, Nina; Taslim,; Irvan,; Manurung, Renita; Tambun, Rondang (Journal of Applied Engineering Science, 2021)
Biofuels as environmentally friendly alternative fuels such as biogasoline, biokerosene and others are generally obtained through a cracking process and take place more effectively to attend a catalyst. In this study, the synthesis of ZnO/ZSM-5 aims to obtain a catalyst that can be used in the cracking process of Palm Methyl Esters (PME) into hydrocarbon fuels especially biogasoline. This catalyst is environmentally friendly, easy to separate, has good selectivity, and can increase the conversion of cracking products. The wet impregnation method followed by drying and calcination is the method used to synthesize the catalyst. Furthermore, several analyzes were carried out to determine the characteristics of the catalyst. The analysis is the Scanning Electron Microscopy-Energy Dispersive X-Ray (SEM-EDX), X-Ray Diffraction (XRD), N2 adsorption-desorption with BET-BJH, Temperature Programmed Desorption-NH3 (TPD-NH3) and the Temperature Programmed Reduction (TPR). Based on synthesis results obtained ZnO/ZSM-5 catalyst with ZnO content of 11.77 wt%, 13.61 wt% and 18.22 wt%. The use of this catalyst in the cracking process can result in the conversion of liquid fuel by 88.57%, heavy hydrocarbon (8.57%) and gas product (2.86%).
Keywords: ZnO/ZSM-5 catalyst, impregnation, cracking, biogasoline